The potential contribution of natural gas to sustainable development in South Eastern Europe - Kovacevic, A (Oxford Institute for Energy Studies, 2007)
South East Europe remains the most underdeveloped region in Europe in terms of energy and energy governance. The region's energy endowment is well below the European average. It is naturally dependent on imports and limited indigenous resources such as hydro, lignite and biomass. Eventual sustainable use of these indigenous resources requires considerable improvements in governance, which is deficient throughout the region.